Применение CFD при проектировании элементов проточной части гидротурбины - Миронов, Константин Анатольевич; Олексенко, Юлия Юрьевна (НТУ "ХПИ", 2016)
Для того чтобы разработать экономически рентабельный проект конструкции гидротурбины, необходимо понять характеристики потока в различных сечениях гидротурбины, что позволит спрогнозировать работу отдельных ее элементов еще до изготовления. В работе показано, что в последнее время CFD широко используется ведущими учеными во всем мире для получения подробной информации о свойствах потока в проточной части гидротурбины с учетом взаимодействия различных ее элементов, а также для прогнозирования работы гидротурбины в целом.

The overall performance of the hydroturbine depends on the individual performance of each component. The change in guide vane opening leads variation in discharge and flow direction, which in turn lead the variation of flow parameters in different components of hydroturbine. Similarly, variation in rotational speed of runner also affects flow characteristics especially in runner. The runner solidity is again important parameter in runner design as it also affects the flow parameters and also performance of hydroturbine. The turbines are designed for particular values of global and local design parameters based on assumptions but most of time, turbine operates at off-design conditions which affects its performance. For cost effective design of the hydroturbine, it is very necessary to understand the flow characteristics in different parts of hydroturbine, which help in predicting their performance before manufacturing. Computational fluid dynamics become a cost effective tool to provide detailed flow information inside the complete hydroturbine space as a whole so that interaction between different components could also be considered. CFD has been widely used by designer and researchers to optimize its design and also as a tool to predict overall performance of Francis turbine.
Application of CFD in design elements flow space of hydroturbine
Keywords: КПД; подвод; рабочее колесо; отсасывающая труба; давление; Francis turbine; hydraulic efficiency; spiral case; draft tube